VISCERAL LEISHMANIASIS: ADULT POPULATION OF ABBOTTABAD AT RISK NOW - Idris, Muhammad; Farid, Jamila; Gul, Nasreen; Rehman, Anis -ur- (Journal of Ayub Medical College Abbottabad, 2010)
Leishmaniasis is a disease complex caused by the parasite of genus Leishmania. Visceral Leishmaniasis is caused by Leishmania donovani transmitted to human by sand fly. Some wild animals and human reservoir is the major reservoir in most of the cases. The disease is prevalent in different parts of the world including India, Nepal, Bangladesh, Sudan and Brazil. It has also been reported from Northern half of Pakistan. In Hazara Division, it has been reported from Galiat, Battagram, Kaladhaka, Kohistan, Balakot, Kaghan and adjoining areas of Azad Jammu & Kashmir. A focus of visceral Leishmaniasis was detected in villages located about 15 Km from Abbottabad city in year 2000. Sporadic cases were reported from the suburbs of Abbottabad but not from Abbottabad city. All these cases and cases from the other parts of Pakistan were children <12 years of age and the disease was not seen in adults except only one child, 11 year old. We report the 1st case from this area which is 16 years old girl. Keywords: Leishmaniasis, Sand fly, LD bodies